Analisis Kandungan Kimia Dan Penetapan Kadar Polifenol Daun Lerak (Sapindus rarak DC) Dengan Metode Spektrofotometri UV-Vis - Salim, Medina; Maryam, St.; Muflihunna, A. (PHARMACY UMI JOURNAL SYSTEM, 2024)
MEDINA SALIM. Chemical Content Analysis and Determination of Lerak Leaf Polyphenol Content (Sapindus rarak DC) by UV-Vis Spectrophotometry Method (Guided by St. Maryam and A. Muflihunna). Lerak contains polyphenolic compounds that reduce blood sugar levels. This study aims to determine the chemical content contained in lerak leaf extract (Sapindus rarak DC) and find out how much polyphenol compounds in the sample. The samples were macerated for 3 days using 96% ethanol solvent, the extraction process was carried out until obtaining an extract yield of 9.323 grams, then two tests were carried out, namely qualitative and quantitative, The qualitative test uses a wet reagent while the quantitative test uses the UV-Vis spectrophotometry method. The maximum wavelength used was 768 nm with gallic acid as a comparison. Based on the study, the results of ethanol extract of lerak leaves (Sapindus rarak DC) contain secondary metabolites, namely saponins, steroids, polyphenols and tannins and the result of polyphenol content is 21,168 mgGAE/g.